(2y+2)*350-(0.6y+6)*350=3500

Simple and best practice solution for (2y+2)*350-(0.6y+6)*350=3500 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2y+2)*350-(0.6y+6)*350=3500 equation:


Simplifying
(2y + 2) * 350 + -1(0.6y + 6) * 350 = 3500

Reorder the terms:
(2 + 2y) * 350 + -1(0.6y + 6) * 350 = 3500

Reorder the terms for easier multiplication:
350(2 + 2y) + -1(0.6y + 6) * 350 = 3500
(2 * 350 + 2y * 350) + -1(0.6y + 6) * 350 = 3500
(700 + 700y) + -1(0.6y + 6) * 350 = 3500

Reorder the terms:
700 + 700y + -1(6 + 0.6y) * 350 = 3500

Reorder the terms for easier multiplication:
700 + 700y + -1 * 350(6 + 0.6y) = 3500

Multiply -1 * 350
700 + 700y + -350(6 + 0.6y) = 3500
700 + 700y + (6 * -350 + 0.6y * -350) = 3500
700 + 700y + (-2100 + -210y) = 3500

Reorder the terms:
700 + -2100 + 700y + -210y = 3500

Combine like terms: 700 + -2100 = -1400
-1400 + 700y + -210y = 3500

Combine like terms: 700y + -210y = 490y
-1400 + 490y = 3500

Solving
-1400 + 490y = 3500

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '1400' to each side of the equation.
-1400 + 1400 + 490y = 3500 + 1400

Combine like terms: -1400 + 1400 = 0
0 + 490y = 3500 + 1400
490y = 3500 + 1400

Combine like terms: 3500 + 1400 = 4900
490y = 4900

Divide each side by '490'.
y = 10

Simplifying
y = 10

See similar equations:

| 12x^3-4x^2=0 | | -11+7t=32+9t | | 35y=280-70x | | 5/x+1/x-3=x-2/x-3 | | -7f/2=-1 | | x=1.25+-0.5y | | x/x^2-25-6/x^2-10+25 | | 5g-7=8g+23 | | ln(x+9)+-1ln(x+-3)=lnx | | ln(x+9)-ln(x-5)=lnx | | 4x^2-3x+60=0 | | 16w^2=225 | | W+16w=225 | | W^2-16w=225 | | W^2+16w=225 | | x+2+6=25 | | 8m^2-18= | | (x+2)-(Y+6)=25 | | 5.2x+19=355 | | 14x-13/12-13x=11/12+3/12 | | Y-7/17=-3/17 | | 1/2y+42/2y-3=9/4y^2+2y-12 | | X+6/17=-7/17 | | 4x+27=110 | | 3(2x-14)+x=15-1(-9x-5) | | (3x^2)-(6x)-144=0 | | 4x-2(8x+1)=-1(2x-10) | | 13d^2-5d=0 | | (x^3)-(3x^2)-144x-140=0 | | x+7=59 | | 6x-12=70 | | 36x^2-8x=0 |

Equations solver categories